Arene C−H Activation at Aluminium(I): meta Selectivity Driven by the Electronics of SNAr Chemistry. Issue 46 (2nd September 2020) - Hicks, Jamie; Vasko, Petra; Heilmann, Andreas; Goicoechea, Jose M.; Aldridge, Simon
Abstract: The reactivity of the electron‐rich anionic Al I aluminyl compound K2 [(NON)Al]2 (NON=4, 5‐bis(2, 6‐diisopropylanilido)‐2, 7‐di‐ tert ‐butyl‐9, 9‐dimethylxanthene) towards mono‐ and disubstituted arenes is reported. C−H activation chemistry with n ‐butylbenzene gives exclusively the product of activation at the arene meta position. Mechanistically, this transformation proceeds in a single step via a concerted Meisenheimer‐type transition state. Selectivity is therefore based on similar electronic factors to classical SN Ar chemistry, which implies the destabilisation of transition states featuring electron‐donating groups in either ortho or para positions. In the cases of toluene and the three isomers of xylene, benzylic C−H activation is also possible, with the product(s) formed reflecting the feasibility (or otherwise) of competing arene C−H activation at a site which is neither ortho nor para to a methyl substituent. Abstract : Exclusive meta selectivity was observed in C−H activation reactions of an electron‐rich Al I aluminyl compound with arenes (see scheme). The selectivity is based on similar electronic factors to those that determine the course of classical SN Ar reactions, which implies the destabilisation of transition states featuring electron‐donating groups in ortho or para positions.